A fluorescent receptor for halide recognition: clues for the design of anion chemosensors1. Issue 16 (28th April 2015) - Chelli, Riccardo; Pietraperzia, Giangaetano; Bencini, Andrea; Giorgi, Claudia; Lippolis, Vito; Salvi, Pier Remigio; Gellini, Cristina
<x xml:space="preserve">Abstract</x> The chemosensing properties for halide ions of a polyammine ligand containing acridine are investigated by fluorescence spectroscopy. The emission is due to acridinium species formed after photoinduced proton transfer.